Hierarchically 3-D Porous Structure of Silk Fibroin-Based Biocomposite Adsorbent for Water Pollutant Removal - Lusi Ernawati (MDPI AG, 2021)
This study explored the tunability of a 3-D porous network in a freeze-dried silk fibroin/soursop seed (SF:SS) polymer composite bioadsorbent. Morphological, physical, electronic, and thermal properties were assessed using scanning electron microscopy, the BET N2 adsorption-desorption test, Fourier transform infrared (FTIR) spectroscopy, and thermogravimetric analysis (TGA). A control mechanism of pore opening–closing by tuning the SS fraction in SF:SS composite was found. The porous formation is apparently due to the amount of phytic acid as a natural cross-linker in SS. The result reveals that a large pore radius is formed using only 20% wt of SS in the composite, i.e., SF:SS (4:1), and the fibrous network closes the pore when the SS fraction increases up to 50%, i.e., SF:SS (1:1). The SF:SS (4:1) with the best physical and thermal properties shows an average pore diameter of 39.19 nm, specific surface area of 19.47 m2·g−1, and thermal stability up to ~450 °C. The removal of the organic molecule and the heavy metal was assessed using crystal violet (CV) dye and the Cu2+ adsorption test, respectively. The adsorption isotherm of both CV and Cu2+ on SF:SS (4:1) follows the Freundlich model, and the adsorption kinetic of CV follows the pseudo-first-order model. The adsorption test indicates that physisorption dominates the adsorption of either CV or Cu2+ on the SF:SS composites.